The carbon footprint of wheat and rice crops in Iraq for the period (2003-2022) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
This research aims to study the impact of the carbon footprint of wheat and rice crops in Iraq for the period (2003-2022). The research assumes that reducing the carbon footprint of agricultural crops through the use of modern technological methods contributes positively to reducing pollution and achieving sustainable agricultural development in Iraq, as the research used methods Descriptive measurement and estimation of the carbon footprint of wheat and rice crops in Iraq during the study period. The research concluded that the total carbon footprint of the wheat crop in Iraq amounted to (510,552,340.1) tons of CO2eq during the study period, which is higher than the carbon footprint of the rice crop, which amounted to (25,191,601.3) tons of CO2eq, which This is attributed to the increase in the cultivated area for wheat compared to the cultivated area for rice. The research also found a fluctuation in the carbon footprint of the two crops (wheat and rice) in Iraq during the study period, as the highest value of the carbon footprint of the wheat crop reached (38,803,322.5) tons of CO2eq in the year (2021) and its lowest value reached (12,931,158.1) tons of CO2eq in the year (2018), as for The carbon footprint of the rice crop reached its highest value (2,096,600.6) tons of CO2eq in the year (2021) and its lowest value (8,878.2) tons of CO2eq in the year (2018), due to the fluctuation in the cultivated area of the crops (wheat and rice) during the period under study, which is attributed to the water crisis that it is suffering from. Including Iraq. The research recommends adopting sustainable agricultural practices in agricultural production operations that depend on reducing greenhouse gas emissions and reducing environmental pollution by replacing fossil fuels with renewable and environmentally friendly energy sources in agricultural operations.